The impact of astaxanthin on adverse effects of hyperglycemia induced by STZ in retinal tissue of rat - Mojarrab, Shahnaz; Bahrami, Farideh; Khoshbaten, Ali; Shojaei, Ahmad; Daftarian, Narsis; Salem, Fatemeh; Mohammadi, Mohammad Taghi (Progress in Nutrition, 2019)
Astaxanthin (ATX) is a powerful natural antioxidant belongs to xanthophylls and the aim of this study is to investigate its protective roles on adverse effects of hyperglycemia in retinal tissue. Sixty rats were randomly divided into Controls, and hyperglycemic groups. ATX (20 mg/kg) was administrated over 47 days. After 47 days the final blood glucose concentration and body weight also the expression of vascular endothelial growth factor (VEGF), tumor necrosis factor α (TNF-α) proteins, antioxidant capacity and vessels dimension in ganglionic cell layer (RGC) layer in retinal tissue were measured as well as immunohistochemistry and histopathological assessments. Hyperglycemia-induced decrement in Catalase (CAT) (0.096 ± 0.026) and Glutathione (GSH) (133.80 ± 65.10) activity in retinal tissue but increase Superoxide dismutase (SOD) (15.52 ± 1.36 mU/mg) and Malondialdehyde (MDA) (2.64 ± 0.12) content. Administration of ATX increased the antioxidant capacity in the treated group (p